Impacting the Cardiac Care of a Nation - Rizzo, Toni (MD Conference Express, 2012)
Cardiovascular disease accounts for 37% of all deaths in Trinidad and Tobago. This article describes the Trinidad and Tobago Health Sciences Cardiovascular Initiative partnership with Johns Hopkins Medicine International to improve cardiovascular care in Trinidad and Tobago.